MONTHLY AVERAGE DISTRIBUTION OF CHLOROPHYLL IN EASTERN SEA FROM AUGUST 2011 TO JULY 2012 - Tác, Vũ Văn (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents the schematic maps describing the distribution of the monthly average chlorophyll content at the surface of the Eastern Sea from August 2011 to July 2012. Each schematic map is a vivid picture describing chlorophyll content through a range of sharp colors, giving readers a visual look on the distribution of chlorophyll content at different points and areas around the Eastern Sea. Thereby, the chlorophyll data, which are interpreted from the remote sensing images of Aqua satellite of National Aeronautics and Space Administration (NASA), are reliable and can be used in the study of primary productivity as well as environmental water quality monitoring.